Carbon sequestration filling material as well as preparation method and application thereof

By using carbon sequestration filling materials prepared by slag, cement and fly ash, the carbon sequestration capacity is improved by using physical adsorption and chemical reactions, the problem of low storage capacity of existing mineralized carbon sequestration materials is solved, and the efficient and low-cost carbon sequestration effect is achieved, and environmental risks are reduced.

CN119661162APending Publication Date: 2025-03-21CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023864.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing mineralized carbon sequestration materials have low carbon sequestration and high cost, and their application is limited.

Method used

Slag, cement and fly ash are used as raw materials to increase the carbon sequestration amount through physical adsorption and chemical reactions, and fill materials with high efficiency carbon sequestration capabilities are prepared.

Benefits of technology

It improves the carbon sequestration capacity of carbon sequestration fill materials, reduces energy consumption and economic costs, has good mechanical properties and durability, and avoids restrictions on the use location and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232174790000041
    Figure BDA0005232174790000041
  • Figure BDA0005232174790000042
    Figure BDA0005232174790000042
Patent Text Reader

Abstract

The invention discloses a carbon sequestration filling material as well as a preparation method and application thereof, and belongs to the technical field of mining industry solid waste treatment and filling materials. The invention provides a preparation method of a carbon sequestration filling material. The preparation method comprises the following steps: stirring slag, cement, fly ash and water to obtain a slag-based filling material; wherein the addition amount of the furnace slag accounts for 50%-80% of the total mass of the furnace slag, the cement and the fly ash, the addition amount of the fly ash accounts for 10%-25% of the total mass of the furnace slag, the cement and the fly ash, and the addition amount of the cement accounts for 10%-25% of the total mass of the furnace slag, the cement and the fly ash; and maintaining the slag-based filling material in a carbon dioxide atmosphere to obtain the carbon sequestration filling material. The carbon sequestration filling material is prepared by taking the furnace slag, the cement and the fly ash as raw materials, and the carbon sequestration quantity is increased by the carbon sequestration filling material through physical adsorption and chemical reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mining solid waste treatment and filling materials, and more specifically to a carbon-fixing filling material and a preparation method and application thereof. Background Art

[0002] As coal mining continues to expand, the resulting ecological damage becomes increasingly prominent. Slag, as solid waste after coal combustion, faces urgent environmental problems in its treatment and disposal. The stacking of slag not only occupies a large amount of land, but also may cause soil and water pollution, emit harmful gases, and affect the surrounding ecology and residents' health. Carbon emissions and solid waste treatment in the coal industry have become urgent issues to be addressed.

[0003] Common carbon sequestration methods include geological storage and mineralization storage. However, geological storage needs to be implemented in areas with good geological conditions and mature technology. Its application is limited by location restrictions and high costs. At the same time, geological storage has environmental risks to a certain extent, including potential leakage risks and groundwater pollution.

[0004] Underground mineralization storage refers to capturing and storing CO2 in flue gas or the atmosphere, and mineralizing and sealing it in the filling body through coal-based solid waste filling materials, thereby reducing the CO2 production in the mining production process, establishing a low-carbon, zero-carbon, negative-carbon green circulation system for mines, and mitigating the greenhouse effect. However, the current carbon storage capacity of mineralized carbon-fixing filling materials is relatively low. Summary of the invention

[0005] In view of the above problems, the present invention provides a carbon-fixing filling material and a preparation method and application thereof. The present invention uses slag, cement and fly ash as raw materials to prepare the carbon-fixing filling material, and the carbon-fixing filling material increases the carbon storage capacity through physical adsorption and chemical reaction.

[0006] The first object of the present invention is to provide a method for preparing a carbon-fixing filling material, comprising the following steps:

[0007] The slag, cement, fly ash and water are mixed to obtain a slag-based filling material; wherein the amount of slag added accounts for 50% to 80% of the total mass of the slag, cement and fly ash, the amount of fly ash added accounts for 10% to 25% of the total mass of the slag, cement and fly ash, and the amount of cement added accounts for 10% to 25% of the total mass of the slag, cement and fly ash.

[0008] For example, the amount of slag added accounts for 50%, 60%, 70%, 80%, etc. of the total mass of slag, cement and fly ash.

[0009] The amount of fly ash added accounts for 10%, 15%, 20%, 25%, etc. of the total mass of slag, cement and fly ash.

[0010] The amount of cement added accounts for 10%, 15%, 20%, 25% etc. of the total mass of slag, cement and fly ash, but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable and will not be repeated here.

[0011] The slag-based filling material is cured under a carbon dioxide atmosphere to obtain a carbon-fixed filling material.

[0012] In a preferred embodiment of the present invention, the amount of slag added accounts for 70% of the total mass of slag, cement and fly ash, the amount of fly ash added accounts for 15% of the total mass of slag, cement and fly ash, and the amount of cement added accounts for 15% of the total mass of slag, cement and fly ash.

[0013] In a preferred embodiment of the present invention, the amount of water added is 20% to 30% of the mass of the slag-based filling material, and the total amount of slag, cement and fly ash added is 70% to 80% of the mass of the slag-based filling material.

[0014] For example, the amount of water added accounts for 20%, 22%, 24%, 26%, 28%, 30%, etc. of the mass of the slag-based filling material.

[0015] The total addition amount of slag, cement and fly ash accounts for 70%, 72%, 74%, 76%, 78%, 80% etc. of the mass of the slag-based filling material, but is not limited to the listed values. Other unlisted values ​​within the above numerical range are also applicable and will not be repeated here.

[0016] In a preferred embodiment of the present invention, an alkali activator is further included, and the amount of the alkali activator added is 0.3% to 0.4% of the total mass of cement and fly ash. For example, the amount of the alkali activator added is 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, and 0.4% of the total mass of cement and fly ash, but it is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and they will not be repeated here.

[0017] In a preferred embodiment of the present invention, the alkaline activator is sodium hydroxide.

[0018] In a preferred embodiment of the present invention, the curing time is 28 to 30 days, for example, the curing time is 28 days, 29 days, or 30 days, but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable and will not be described one by one here.

[0019] In a preferred embodiment of the present invention, during curing, the humidity is 80% to 85%, and the carbon dioxide concentration is 20% to 25%.

[0020] For example, the humidity is 80%, 81%, 82%, 83%, 84%, 85%, etc.

[0021] The carbon dioxide concentration is 20%, 21%, 22%, 23%, 24%, 25%, etc., but is not limited to the listed values. Other unlisted values ​​within the above numerical range are also applicable and will not be repeated here.

[0022] The second object of the present invention is to provide a carbon-fixing filling material prepared by the above preparation method.

[0023] The third object of the present invention is to provide the use of the above-mentioned carbon-fixing filling material in underground filling and carbon fixation.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention uses slag, cement and fly ash as raw materials to prepare carbon-fixing filling materials. The slag is rich in various alkaline oxides and has a higher specific surface area and porosity. It achieves efficient carbon fixation through mineralization reaction and physical adsorption, reducing energy consumption and the economic cost of the carbon fixation process; the calcium and magnesium alkaline components in cement and fly ash react with CO2 and water to form calcium carbonate, etc., which improves the carbon fixation capacity through chemical reactions. The present invention improves the carbon fixation capacity of the carbon-fixing filling material through physical adsorption and chemical reaction.

[0026] (2) The carbon-fixing filling material prepared by the present invention has good mechanical properties and shows good durability and chemical stability in long-term use. It also has strong adaptability and can be used in different regions and conditions, avoiding restrictions on the use location and the problems of leakage and groundwater pollution. The present invention uses slag as raw material, which changes the traditional concept of slag as waste, gives it new functions, reduces the environmental burden of industrial solid waste, improves the resource utilization rate of solid waste, and helps achieve sustainable development goals. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] There are a lot of alkaline oxides in the slag, which can react with gases such as carbon dioxide to achieve carbon fixation. At the same time, the porous structure medium material has a certain adsorption effect on gases such as carbon dioxide. The present invention uses sodium hydroxide as an alkali activator, and the calcium and magnesium alkaline components in cement and fly ash react with CO2 and water to form calcium carbonate, etc. The slag is used as a porous medium aggregate. In the carbon fixation process, the gas adsorption effect is strong, which can increase the carbon fixation efficiency and the amount of free CO2 sealed.

[0029] The carbon-fixing filling material prepared by the present invention can be used in synergistic treatment with power plant flue gas, which can not only effectively achieve the reduction, harmlessness and resource utilization of solid waste, but also reduce the emission of gaseous pollutants in the carbon fixation process, achieve a win-win situation, promote green development, and provide a new method for the effective treatment of coal-based solid waste.

[0030] The cement used in the present invention is composite silicate cement PO42.5, and the strength is 42.5MPa.

[0031] The chemical composition and content of the slag used in the present invention are shown in Table 1.

[0032] Table 1 Main chemical composition and content of slag

[0033]

[0034] The chemical composition and content of the fly ash used in the present invention are shown in Table 2.

[0035] Table 2 Main chemical composition and content of fly ash

[0036]

[0037] Example 1

[0038] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0039] Step 1, firstly, 56 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the slag composition of 0-1 mm accounts for 60% of the total slag; the aggregates are added into a mixing tank with a stirring device and stirred for 2 minutes; then 12 parts of fly ash and 12 parts of cement are added, and after adding 20 parts of water, the mixture is stirred for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0040] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0041] Example 2

[0042] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0043] Step 1, firstly, 56 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the content of slag with a slag composition of 0-1 mm accounts for 60% of the total amount of slag; the aggregates and 0.1 parts of sodium hydroxide admixture are added to a stirring tank with a stirring device and stirred for 2 minutes; then 12 parts of fly ash, 12 parts of cement, and 20 parts of water are added, and the stirring is continued for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0044] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0045] Example 3

[0046] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0047] Step 1, firstly, 48 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the content of slag with a slag composition of 0-1 mm accounts for 60% of the total amount of slag; the aggregates and 0.1 parts of sodium hydroxide admixture are added into a stirring tank with a stirring device and stirred for 2 minutes; then 16 parts of fly ash and 16 parts of cement are added, and after adding 20 parts of water, stirring is continued for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0048] Step 2: Take out the material and put it into a carbon dioxide curing box at room temperature, with a humidity of 80% and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixing filling material is obtained.

[0049] Example 4

[0050] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0051] Step 1, firstly, 56 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the slag composition of 0-1 mm accounts for 60% of the total slag; the aggregates are added into a mixing tank with a stirring device and stirred for 2 minutes; then 12 parts of fly ash and 12 parts of cement are added, and after adding 20 parts of water, stirring is continued for 2 minutes at a stirring speed of 400 r / min to prepare a slag-based filling material;

[0052] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0053] Example 5

[0054] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0055] Step 1, firstly, 48 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the content of slag with a slag composition of 0-1 mm accounts for 60% of the total amount of slag; the aggregates are added into a mixing tank with a stirring device and stirred for 2 minutes; then 16 parts of fly ash and 16 parts of cement are added, and after adding 20 parts of water, stirring is continued for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0056] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0057] Example 6

[0058] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0059] Step 1, first sieve 35 parts of slag into aggregates with a particle size of 0-5 mm, wherein the slag composition is 0-1 mm slag content accounts for 60% of the total slag; add the aggregate and 0.1 parts of sodium hydroxide admixture into a stirring tank with a stirring device and start stirring for 2 minutes; then add 17.5 parts of fly ash, 17.5 parts of cement, and after adding 30 parts of water, continue stirring for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0060] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 85%, and a carbon dioxide concentration of 25%. After 30 days of curing, a carbon-fixed filling material is obtained.

[0061] Example 7

[0062] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0063] Step 1, firstly, 47 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the content of slag with a slag composition of 0-1 mm accounts for 60% of the total amount of slag; the aggregates and 0.1 parts of sodium hydroxide admixture are added into a stirring tank with a stirring device and stirred for 2 minutes; then 14 parts of fly ash, 14 parts of cement, and 25 parts of water are added, and the stirring is continued for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0064] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 83%, and a carbon dioxide concentration of 22%. After 29 days of curing, a carbon-fixed filling material is obtained.

[0065] Example 8

[0066] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0067] Step 1, first sieve 72 parts of slag into aggregates with a particle size of 0-5 mm, wherein the slag composition of 0-1 mm accounts for 60% of the total slag; add the aggregates and 0.06 parts of sodium hydroxide admixture into a stirring tank with a stirring device and start stirring for 2 minutes; then add 9 parts of fly ash and 9 parts of cement, add 30 parts of water, and continue stirring for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0068] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0069] Example 9

[0070] This embodiment provides a method for preparing a carbon-fixing filling material, comprising the following steps:

[0071] Step 1, firstly, 48 parts of slag are screened into aggregates with a particle size of 0-5 mm, wherein the content of slag with a slag composition of 0-1 mm accounts for 60% of the total amount of slag; the aggregates and 0.1 parts of sodium hydroxide admixture are added into a stirring tank with a stirring device and stirred for 2 minutes; then 24 parts of fly ash and 8 parts of cement are added, and after adding 10 parts of water, stirring is continued for 2 minutes at a stirring speed of 100 r / min to prepare a slag-based filling material;

[0072] Step 2: Take out the slag-based filling material and put it into a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, a carbon-fixed filling material is obtained.

[0073] Comparative Example 1

[0074] This comparative example provides a method for preparing a gangue-based carbon-fixing filling material, comprising the following steps:

[0075] Step 1, firstly crush and screen 45 parts of coal gangue into aggregates with a particle size of 0-5 mm, wherein the content of coal gangue with a slag composition of 0-1 mm accounts for 60% of the total amount of coal gangue; add the aggregates into a mixing tank with a stirring device and start stirring for 2 minutes; then add 12 parts of fly ash and 12 parts of cement, add 20 parts of water, and continue stirring for 2 minutes at a stirring speed of 100 r / min to prepare the gangue-based filling material;

[0076] The gangue-based filling material is taken out and placed in a carbon dioxide curing box at room temperature, a humidity of 80%, and a carbon dioxide concentration of 20%. After 28 days of curing, the gangue-based carbon-fixing filling material is obtained.

[0077] When the prepared slag-based porous medium carbon-fixing filling material is tested in the present invention, the compressive strength test method is tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T 50081-2019, and the carbon fixation capacity is tested by thermogravimetric analysis at a temperature of 1000°C.

[0078] Table 3 Performance test results of carbon-fixing filling materials

[0079] Group 28-day compressive strength / MPa Carbon fixation capacity / % Example 1 3.65 3.882 Example 2 3.81 4.256 Example 3 3.78 4.068 Example 4 3.57 3.943 Example 5 3.94 3.946 Comparative Example 1 3.23 3.143

[0080] All embodiments were tested for 28-day uniaxial compressive strength and carbon fixation capacity; from the test results in Table 3, it can be found that the 28-day compressive strength of the carbon-fixing filling material is greater than 3MPa. Compared with Example 1, the carbon fixation capacity of the carbon-fixing filling material in Example 2-4 is higher than that in Example 1, indicating that the performance of the carbon-fixing filling material of the present invention is relatively excellent, and the selection of a suitable raw material ratio, stirring speed and a suitable admixture can improve the carbon fixation capacity of the carbon-fixing filling material. Compared with Example 1, the law of increase / decrease in carbon fixation in Example 2-4 is as follows: increase in slag content, increase in fly ash content, increase in stirring rate, and addition of admixtures can all increase carbon fixation. The increase in slag content leads to an increase in carbon fixation because slag belongs to a porous medium material, which acts as an aggregate of the carbon-fixing filling material and increases the gas adsorption performance of the material as a whole. The increase in fly ash content leads to an increase in carbon fixation because the CaO content in the fly ash increases, which can react with more CO2 gas, thereby increasing the chemical carbon fixation. The increase in stirring rate leads to an increase in carbon fixation because the contact area between the slurry and the flue gas is increased. The increase in carbon fixation due to the addition of admixtures is due to the increase in alkaline metal oxides in the slurry, which increases the carbon fixation through chemical reactions. Compared with Example 1 and Example 5, Example 5 changes the material ratio, reduces the slag aggregate component, increases the fly ash and cement ratio, increases cement, and improves strength. The CaO component in cement and fly ash is relatively high, which increases the chemical reaction carbon fixation capacity in the material, thereby increasing the carbon fixation capacity. In Comparative Example 1, the slag aggregate is replaced with coal gangue, and the compressive strength and carbon fixation capacity are reduced. This is because the gas adsorption capacity of coal gangue is lower than that of slag, and its CaO content is also lower than that of slag. The physical adsorption and chemical reaction amount are both less than the carbon-fixing filling material prepared with slag as raw material in the present invention.

[0081] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0082] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a carbon-fixing filling material, characterized in that: The following steps are involved: The slag, cement, fly ash and water are mixed to obtain a slag-based filling material; wherein the amount of slag added is 50% to 80% of the total mass of the slag, cement and fly ash, the amount of fly ash added is 10% to 25% of the total mass of the slag, cement and fly ash, and the amount of cement added is 10% to 25% of the total mass of the slag, cement and fly ash; The slag-based filling material is cured under a carbon dioxide atmosphere to obtain a carbon-fixed filling material.

2. The method for preparing a slag-based porous medium carbon-fixing filling material according to claim 1, characterized in that: The amount of slag added accounts for 70% of the total mass of slag, cement and fly ash, the amount of fly ash added accounts for 15% of the total mass of slag, cement and fly ash, and the amount of cement added accounts for 15% of the total mass of slag, cement and fly ash.

3. The method for preparing a carbon-fixing filling material according to claim 1, characterized in that: The amount of water added accounts for 20% to 30% of the mass of the slag-based filling material, and the total amount of slag, cement and fly ash added accounts for 70% to 80% of the mass of the slag-based filling material.

4. The method for preparing a carbon-fixing filling material according to claim 1, characterized in that: The invention also comprises an alkali activator, the addition amount of which is 0.3% to 0.4% of the total mass of cement and fly ash.

5. The method for preparing a carbon-fixing filling material according to claim 4, characterized in that: The alkaline activator is sodium hydroxide.

6. The method for preparing a carbon-fixing filling material according to claim 1, characterized in that: The maintenance time is 28 to 30 days.

7. The method for preparing a carbon-fixing filling material according to claim 1, characterized in that: During maintenance, the humidity is 80% to 85% and the carbon dioxide concentration is 20% to 25%.

8. A carbon-fixing filling material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carbon-fixing filling material according to claim 8 in underground filling and carbon fixation.